Mutagenesis Analysis of ABCG2 Gene Promoter of Zebrafish (Danio Rerio) - Nabila Zurain, Md Yusni; Chung, Hung Hui; Whye, Leonard Kit Lim (UNIMAS Publisher, 2020)
Breast cancer is the commonest cancer among women worldwide and the probability of a woman dying from breast cancer is high (about 1 in 38 of total human population (2.6%)).The main factor for mortality is due to the resistance of this particular disease to chemotherapeutic agents. One of the most well-known proteins to be found to correlate significantly with breast cancer resistance to chemotherapeutic agent is the ATP-binding cassette super-family G member 2 (ABCG2). Knowledge on ABCG2 gene regulation is still lacking in terms of how the increased cytotoxic levels are closely related to induce a hype in gene transcript levels and ultimately cause of the reduction in chemotherapeutic agents. The approach taken in this study is through mutational analysis of selected transcription factor governing the expression of ABCG2. In order to achieve this, a previously cloned ABCG2 promoter which has been isolated (around 1500 bp in size) from Danio rerio and inserted into pGL3.0 plasmid, was subjected to site-directed mutagenesis. Selected transcription factor which is AP-1 was successfully mutated by deletion of 5'- TGACGCG -3' sequence at position 1113 bp from TSS+1 where it would bind in order to define their role in ABCG2 physiological function. Sequencing result after site-directed mutagenesis shows high similarities about 98% with ABCG2 gene of Danio rerio. Upon validation, it was found that the intended AP-1 binding site has been mutated. In future work, the mutated clone here will be subjected to transfection analysis where dual-luciferase assay will be conducted to verify the loss of activity from the ABCG2 promoter upon mutation of the targeted AP-1 site. Hence, the mutagenesis analysis of ABCG2 promoter are able to provide information on the involvement of AP-1 transcription factor in multidrug resistance mechanism of breast cancer and thus will be a potential target for chemotherapeutic agent.